A Mapping Research on Cofiring from 1979 - 2022: Bibliometric Analysis - Muhammad Farras Ilham; Muchammad; Marcelinus Christwardana (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate cofiring-themed articles through Bibliometric analysis using Biblioshiny. The metadata comes from the Scopus database, obtained using the keyword